2008
DOI: 10.1073/pnas.0706473105
|View full text |Cite
|
Sign up to set email alerts
|

Leptin responsiveness restored by amylin agonism in diet-induced obesity: Evidence from nonclinical and clinical studies

Abstract: Body weight is regulated by complex neurohormonal interactions between endocrine signals of long-term adiposity (e.g., leptin, a hypothalamic signal) and short-term satiety (e.g., amylin, a hindbrain signal). We report that concurrent peripheral administration of amylin and leptin elicits synergistic, fat-specific weight loss in leptin-resistant, diet-induced obese rats. Weight loss synergy was specific to amylin treatment, compared with other anorexigenic peptides, and dissociable from amylin's effect on food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
385
1
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 392 publications
(413 citation statements)
references
References 40 publications
23
385
1
4
Order By: Relevance
“…The present studies extend emerging literature, where additive or synergistic interactions are reported for amylin in 32 and leptin), 40,41 to include small molecule agents that act via classic neurotransmitters. Consistent with the results reported here, co-administration of the amylin agonist pramlintide with sibutramine or phentermine in a clinical trial has recently been reported to result in increased weight loss in obese subjects.…”
Section: Discussionsupporting
confidence: 70%
“…The present studies extend emerging literature, where additive or synergistic interactions are reported for amylin in 32 and leptin), 40,41 to include small molecule agents that act via classic neurotransmitters. Consistent with the results reported here, co-administration of the amylin agonist pramlintide with sibutramine or phentermine in a clinical trial has recently been reported to result in increased weight loss in obese subjects.…”
Section: Discussionsupporting
confidence: 70%
“…It is known that a co-infusion of amylin and leptin reduces body weight and adiposity synergistically in DIO prone rats [22]. Additionally, it has been shown that peripheral administration of amylin restores leptin sensitivity in obese rats and humans [33]. These findings suggest that an interaction exists between exogenous amylin and the prevailing circulating leptin values.…”
Section: Amylin-induced Suppression Of Energy Intake Is Decreased Aftmentioning
confidence: 56%
“…Furthermore, because of the known interaction between amylin and leptin [22,33], we determined whether an increase of amylin, independent of obesity, alters circulating leptin levels. Again we observed that as circulating amylin levels increased, there was a trend toward a decrease in leptin levels.…”
Section: Hyperamylinemia Alone Does Not Cause Amylin Insensitivitymentioning
confidence: 99%
“…Interestingly, recent studies suggest that amylin interacts with leptin, possibly at the level of the VMH and the Arc. Amylin pretreatment partially restored hypothalamic leptin sensitivity in leptin resistant diet-induced obese rats in the VMH (Roth et al, 2008) and increased leptin sensitivity also in lean rats (Turek et al, 2010). These effects have been suggested to depend on polysynaptic connections from the AP to the VMH and the Arc (Roth et al, 2008;Turek et al, 2010).…”
Section: Functional Considerationsmentioning
confidence: 99%
“…Amylin pretreatment partially restored hypothalamic leptin sensitivity in leptin resistant diet-induced obese rats in the VMH (Roth et al, 2008) and increased leptin sensitivity also in lean rats (Turek et al, 2010). These effects have been suggested to depend on polysynaptic connections from the AP to the VMH and the Arc (Roth et al, 2008;Turek et al, 2010). Our demonstration of very dense projections from the amylin-activated LPB region to the VMH and the Arc (Supplementary Results and Fig.…”
Section: Functional Considerationsmentioning
confidence: 99%